Some outlier problems in a circular regression model / Safwati binti Ibrahim - Ibrahim, Safwati (2013)
This study looks at three problems related to the JS circular regression model with five objectives in mind. The first two objectives are concerned with the problem of outliers in the model. The first is the investigation of the robustness of the JS circular regression estimation method in the presence of outliers in the data set. The second is the use of three numerical tests based on row deletion approach to detect possible outliers in the JS circular regression model. The first test considered is a modified version of the COVRATIO statistic by utilizing the covariance matrix of residuals of the JS circular regression model. The other tests are based on the difference mean circular error statistics using cosine and sine functions. For each test, the generation of cut-off points and the power of performance are presented via simulation. In general, the three numerical tests perform well in detecting outliers in JS circular regression model.